2016
DOI: 10.1155/2016/2652174
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Diversity of Pretibial Myxedema and Its Mechanism of Evolving Process and Outcome: A Retrospective Study of 216 Cases

Abstract: Background. Pretibial myxedema (PTM) is a rare dermopathy. The morphologic features and mechanism of its evolving process are not reported in large case series. Methods. 216 cases with PTM were retrospectively reviewed to analyze demographics, history, lesional morphology and its evolving process, histopathology and immunohistochemistry, serum TRAb levels, treatment, and outcome. Results. First appearing lesions evolved into 6 variants that were correlated with serum TRAb levels. Subvariants were caused by dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…A definite diagnosis for PTM was made under the background of thyroid diseases or thyroid disease history, the presence of typical skin lesions, or atypical skin lesions (atypical locations and atypical appearances) plus histopathology of mucinous degeneration and positive Alcian blue staining in the dermis (modified from [6] and [14]). GD was diagnosed on the basis of clinical and/or biochemical evidence of thyrotoxicosis plus one or more of the following features: serum TRAb positive, thyroid-associated ophthalmopathy and/or dermopathy and/or acropachy, hypoechoic and increase in vascularity shown by thyroid ultrasound with Doppler, and diffuse elevated radioactive iodine uptake (RAIU).…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…A definite diagnosis for PTM was made under the background of thyroid diseases or thyroid disease history, the presence of typical skin lesions, or atypical skin lesions (atypical locations and atypical appearances) plus histopathology of mucinous degeneration and positive Alcian blue staining in the dermis (modified from [6] and [14]). GD was diagnosed on the basis of clinical and/or biochemical evidence of thyrotoxicosis plus one or more of the following features: serum TRAb positive, thyroid-associated ophthalmopathy and/or dermopathy and/or acropachy, hypoechoic and increase in vascularity shown by thyroid ultrasound with Doppler, and diffuse elevated radioactive iodine uptake (RAIU).…”
Section: Participantsmentioning
confidence: 99%
“…Multiple modalities of PTM treatment have been reported that include minimizing risk factors (smoking, obesity), topical steroids, intralesional steroids (triamcinolone, betamethasone) [34], plasmapheresis, intravenous immunoglobulin (IVIg), surgery [35], UVA1, compression bandages, and massage therapy. Glucocorticoid inhibiting TSHR autoimmunity and HA synthesis can lower serum TRAb levels and improve PTM [6,36]. Rituximab (RTX) and IVIg have recently been reported to achieve improvement or stability of PTM.…”
Section: Diagnosis and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…This progression was correlated with TSH-R antibody titers and the degree of perivascular lymphocytic infiltration. 7 …”
Section: Discussionmentioning
confidence: 99%
“…Once every seven days is a better regimen. Lan et al[ 10 ] also performed a retrospective study. An intralesional glucocorticoid was used and the dosage of triamcinolone acetonide acetate was 50 mg/5 mL.…”
Section: Discussionmentioning
confidence: 99%